A Constructive Leadership Framework from a Reflective Value of Local Wisdom for Education Reform in Aceh, Indonesia - Alfiatunnur; Mike Hardy; Sariya Cheruvallil (Journal of Islamic Mental Health and Development, 2026)
The research findings from semi-structured in-depth interviews and focus group discussions unequivocally support a constructive leadership framework grounded in local wisdom. This framework underscores the necessity of understanding the philosophical foundation of local wisdom, which is deeply rooted in Aceh's historical context, encompassing the sultanate's reign, the Dutch colonial War, past Conflicts, disasters, and the Peace Agreement. Additionally, this framework is vital for a thorough understanding of the influence of religion, as well as the imperative leadership skills, a robust academic background, and the passion and experience essential in education. Ultimately, this constructive framework is poised to drive significant reforms in education across Aceh, particularly in the aftermath of conflict and disaster, and is firmly grounded in local wisdom